Static voltage stability analysis and evaluation of vector controlled offshore wind farm considering cable capacitance parameters - Tan, Hongtao; Li, Hui; Yao, Ran; Liu, Renkuan; Zhou, Zhiting; Zhang, Xiuqi (Frontiers in Energy Research, 2023)
Voltage stability region assessment is the key to ensuring the reliable operation of offshore wind farms (FWFs). However, the traditional analysis method, which treats the WFs as a PQ node and directly connected to the infinite power grid, fails to take the cable capacitance and the dynamics of the converter into account, resulting an inaccurate evaluation of voltage stability. The contribution of this paper is to propose a more accurate method for assessing the voltage stability of FWFs. Firstly, based on the equivalent circuit method, the point of common coupling (PCC) and internal voltage characterization models of FWF considering the cable capacitance parameters are derived. Then, the coupling interface between the dynamic of the converter and the voltage characteristics of the system is designed, and the transfer function of the power injection from the DC side of the converter to the voltage of the collector system is established, which fully reflects the OWF Pin→Udc→Id→Upcc→Pout transitive relationship. Finally, a voltage stability criterion based on dPw, out/dId&dUdc/dt direction discrimination is proposed, and the influence of cable parameters, output power, and grid impedance on the voltage stability margin is analyzed. The accuracy of the proposed method is verified based on the RT-LAB platform.